2009
DOI: 10.1677/joe-09-0379
|View full text |Cite
|
Sign up to set email alerts
|

The importance of ERβ signalling in the ovary

Abstract: This review examines the evidence for a central role of oestrogen receptor b (ERb or ESR2 as listed in the MGI Database) in folliculogenesis and hence reproductive biology. Knockout mouse models have been a valuable resource in this respect. The ERb-null mouse exhibits a granulosa cell phenotype associated with the partial arrest of folliculogenesis and ovulatory dysfunction. Phyto-oestrogens such as genistein, which preferentially activate ERb, have been shown to alleviate the ovarian phenotype of the oestrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 132 publications
3
90
0
Order By: Relevance
“…An interesting finding in this respect is the fact that nonclassical estrogen signaling has been shown previously to interact with the MAPK pathway 31 -a signaling pathway involved in the earliest stages of gonadal developmentalthough the operating mechanisms are different in humans and mice. In humans, MAPK signaling is essential for tilting the gene expression balance towards SOX9 expression; gain- of-function mutations of MAP3K1 lead to higher phosphorylation of downstream targets, causing decreased expression of SOX9 and increased expression of female-specific genes like β-catenin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting finding in this respect is the fact that nonclassical estrogen signaling has been shown previously to interact with the MAPK pathway 31 -a signaling pathway involved in the earliest stages of gonadal developmentalthough the operating mechanisms are different in humans and mice. In humans, MAPK signaling is essential for tilting the gene expression balance towards SOX9 expression; gain- of-function mutations of MAP3K1 lead to higher phosphorylation of downstream targets, causing decreased expression of SOX9 and increased expression of female-specific genes like β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, MAPK signaling is essential for tilting the gene expression balance towards SOX9 expression; gain- of-function mutations of MAP3K1 lead to higher phosphorylation of downstream targets, causing decreased expression of SOX9 and increased expression of female-specific genes like β-catenin. 2,31,32 In mice, the Mapk pathway acts through direct upregulation of Sry; homozygous loss-of-function variants of Map3k4 are reflected in a male-to-female sex reversal phenotype. 3,33 Nuclear receptor family members, to which the ERs belong, are known to exert their functions through different action mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, gene silencing with siRNAs for individual receptor subtypes confirmed that these effects were mediated via the respective receptors, without significant cross-reaction with the other subtype. The molecular pathways involved in the activation of ERa are well reported but the pathways involved in ERb activation are much less well established (Drummond & Fuller 2010). Therefore in this study, we also attempted to elucidate the molecular pathways involved.…”
Section: Discussionmentioning
confidence: 99%
“…ESR1 is expressed primarily in theca cells, and ESR2 is expressed in granulosa cells and essential for FSH-directed granulosa cell differentiation as well as for LH responsiveness [90,91]. ESR2 also facilitates mechanisms that promote follicle maturation from the early antral to the preovulatory stages [92,93]. In addition it may play a major role in primordial follicle formation in the ovary [93 -97].…”
Section: Expression Patterns and Roles Of Ers In The Ovaries And Uterimentioning
confidence: 99%